Prevalence of anti-S100A10 antibodies in antiphospholipid syndrome patients. Issue 179 (July 2019) - Salle, V.; Sagnier, A.; Diouf, M.; Schmidt, J.; Smail, A.; Galmiche, A.; Herpe, Y.E.; Duhaut, P.
Abstract: Introduction: Annexin A2 (ANXA2), an endothelial cell receptor for plasminogen and tissue plasminogen activator, has been identified as a new autoantigen in antiphospholipid syndrome (APS). ANXA2 can exist as a monomer or a heterotetrameric complex with S100A10 protein. This S100A10 subunit also plays a pivotal role in the regulation of fibrinolysis. The aim of this study was to evaluate the prevalence of autoantibodies directed against S100A10 protein in patients with APS. Methods: Patients with primary antiphospholipid syndrome (PAPS), patients with systemic lupus erythematosus (SLE) and patients with unexplained thrombosis were retrospectively included in this study. Patients were followed in the department of Internal Medicine of Amiens University Hospital, Amiens, France. IgG and IgM anti-S100A10 antibodies were detected in the serum of patients by enzyme-linked immunosorbent assay. The cut-off value for positivity was defined as 3 standard deviations above the mean optical density (OD) obtained in the sera of 116 healthy blood donors. Results: The study group consisted of 116 healthy individuals and 106 patients: 42 APS patients (26 patients with PAPS and 16 patients with secondary SLE-related APS), 43 SLE patients without APS and 21 patients with unexplained thrombosis. The median age of APS patients, SLE patients without APS, patients with unexplained thrombosis and healthy individuals was 47, 38, 53 and 42 years, respectively. Anti-S100A10 antibodies were detected in 11.9% of APS patients and this prevalence was statistically higher than that observed in healthy individuals (1.7%) (p = 0.0148). Highest levels of anti-S100A10 were observed in the serum of one PAPS patient with venous thrombosis and one SLE patient with APS with a history of stroke and recurrent miscarriage. Conclusion: S100A10 protein, the binding partner of ANXA2, was identified as a target of autoantibodies in sera from patients with APS. Further studies involving a large cohort of APS patients are required to determine whether these antibodies could play a role in thrombogenic mechanisms of APS and to determine their diagnostic value in discriminating clinical subgroups of patients with APS, particularly those with seronegative APS. Highlights: S100A10 is a binding partner of annexin A2 S100A10 plays a pivotal role in regulation of fibrinolysis S10010 has been identified as a new autoantigen in antiphospholipid syndrome The prevalence of anti-S100A10 in APS patients (11.9%) was statistically higher than in control group (1.7%) Further studies in large cohort of APS patients are needed to determine whether these antibodies could be pathogenic